Analysis of user satisfaction with primary healthcare services in Morocco: the case of diabetic patients in the town of Tiznit - HOUMAM, Idriss; El Bouzidi, Mohamed; BACHAR, Redouane; Essaadouney, Khadija; Boullah, Maryam (Revue Internationale du Chercheur, 2025)
This study deals with a fundamental aspect of the quality of health services: the satisfaction of primary care users. To this end, an analysis of the quality of the healthcare supply and the satisfaction of diabetic patients in Morocco was carried out. This is a confirmatory descriptive quantitative study carried out in urban health centers in Tiznit. The aim was to identify the factors influencing user satisfaction with primary healthcare for diabetic patients. To this end, a self-administered questionnaire was designed to collect the data. The sample selected was n = 60 . The data were processed and analyzed using JAMOVI software. The study's results reveal a significant association between age and level of satisfaction (p = 0.03). There was also a significant association between satisfaction and healthcare facilities. Regarding accessibility to healthcare facilities, the results reveal a significant correlation with satisfaction (P=0.009). It is essential to consider these factors in the care approach to increase the satisfaction level of diabetic patients and improve the quality of the services offered.